Mengkaji Dampak Dukungan Sosial, Optimisme, Religius, Dan Harga Diri Terhadap Kesejahteraan Subyektif Guru - Yuin, Komang; Agung, Anak Agung Gede; Dantes, Kadek Rihendra (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This study aims to assess the extent to which social support, optimism, religiosity, and self-esteem contribute to the subjective well-being of teachers in SMPNs across Mendoyo District. Additionally, it seeks to determine the combined impact of these factors on teachers' subjective well-being. This study is an "ex post facto" research study conducted with a sample size of 164 individuals. Information was gathered through the use of questionnaires and documents. The data analysis was conducted using simple regression, multiple regression, and partial correlation approaches. The research findings indicate a strong association (correlation coefficient of 0.319) and a notable contribution (16.11%) of social support to the subjective well-being of teachers in SMPNs in the Mendoyo District. (2) A notable distinction exists between optimism and the subjective well-being of instructors in SMPN within Mendoyo District, as evidenced by a correlation coefficient of 0.364 and a substantial contribution of 18.05%. (3) There is a strong relationship between how religious teachers are and how satisfied they feel in SMPN schools in Mendoyo District. This relationship is measured by a correlation coefficient of 0.519, indicating a moderate positive correlation. Religiosity accounts for 37.66% of the variation in teachers' subjective well-being. (4) There is a strong relationship between the self-esteem and subjective well-being of instructors in SMPN throughout Mendoyo District. The correlation coefficient is 0.387, indicating a substantial connection. Additionally, self-esteem accounts for 19.98% of the overall impact on subjective well-being. (5) The study found a strong relationship between social support, optimism, religiosity, and self-esteem with the subjective well-being of SMPN teachers in Mendoyo District. The multiple correlation coefficient was 0.960, indicating a high degree of association. These factors accounted for 92.44% of the variation in the subjective well-being of SMPN teachers across Mendoyo District.